A review of methods for quantifying secondary organic aerosol - M* Zheng; CQ Yan; XX Li; XS Wang; Zhang, Y. H. (China Environmental Science, 2014)
Regional air pollution is complex and becomes increasingly important in China.Among many others,secondary organic aerosol(SOA) is one of the most important components of PM2.5.This paper discusses various methods for quantifying SOA in the atmosphere(including methods based on the EC tracer,WSOC,receptor model,the SOA tracers,and air quality model),presents the basic principle of each method and points out that 1) the EC-tracer method,the WSOC method and the receptor model method are relatively simple and convenient,but limited by the availability of local source profiles and some specific tracers;2) the SOA-tracer method is analytically challenging but can supply source-specific SOA information;and 3) the air quality model method can provide large scale spatial distribution of SOA.This paper also summarizes the most recent results of SOA research in China and abroad and indicates that SOA is important in organic aerosol,and anthropogenic VOCs play a significant role in SOA formation in China.The primary purpose of this review is to provide basic and integrated information and suggestion for future directions of SOA study in China.